Bridging Digital Technology and Local Heritage: An E-Magazine Model for Contextual History Learning in Post-Colonial Urban Spaces - Muhammad Bagas Riyanto; Abdul Rozaq; Dafina Pramuditya; Hany Nurpratiwi; Yudi Pratama (Indonesian Journal of History Education, 2025)
This study develops and evaluates "SERAYA," a digital e-magazine integrated with Google Street View, designed as an innovative medium for cultural heritage education and local history learning in Semarang, Indonesia. Employing the Research and Development (R&D) method with the ADDIE model, the research involved needs analysis, expert validation, and a limited trial with 30 members of a historical organization. Results from material and media expert validation confirmed the product's high feasibility. User trials indicated that SERAYA effectively enhanced understanding of Semarang's history and culture, raised awareness of heritage preservation, and stimulated interest in visiting historical sites. The integration of Google Street View provides dynamic, cost-effective visual documentation, supporting sustainable monitoring. This study contributes to the discourse on media innovation in history education by offering a replicable model that leverages digital technology to foster historical literacy, connect communities with local heritage, and support preservation in a post-colonial urban context.